UPDATING CONCEPTUAL MODEL OF ULUMBU GEOTHERMAL FIELD USING NUMERICAL SIMULATION - Karunia Hammad, Fadhil
The Ulumbu geothermal field is the most promising prospect on the island of Flores from government program, which has a temperature of 230-250 ? with steam cap overlying liquid dominated reservoir and possible reserve of 103 MWe from based on previous study. Model reservoir need to be updated comprehensively and periodically according to the latest data. Therefore, reservoir simulations and reservoir characteristics were compared with previous studies to mitigate risks in exploitation and update the conceptual model. The Numerical Reservoir model was carried out by using the TOUGH2 V.2.0 EOS 1 simulator with two calibration stages, natural state and historical mathcing. RMSE calculations are done to determine the deviation value in the observation data. The results indicate has alignment between the simulation model and field data. Calibration results showed good agreement between the model simulation and observation data. The results were compared with the previous model, which had natural state calibration, revealing differences in heat distribution, mass distribution, and fluid saturation conditions. These differences may be due to the availability of more recent data, making the model results more representative. Consequently, an update to the conceptual model was carried out based on geoscience studies and well data.